PERIPHERAL OSSFYING FIBROMA IN THE SIX YEARS OLD CAT - Simanihuruk, Brigietta Vincencia; Arjentinia, I Putu Gede Yudhi; Putriningsih, Putu Ayu Sisyawati (Buletin Veteriner Udayana, 2025)
Cats are not immune to various types of diseases that can cause lesions, including oral lesions. Oral lesions are common in cats. This report aims to discuss the results of anamnesis, physical examination, and supporting examination in a six-year-old case cat with nasal discharge and watery eyes that had lasted for seven months. The cat's pre-existing status showed normal physiologic data. Physical examination found swelling on the left side of the cat's face, yellowish discharge from the eye and nose from the left side and swollen left mandibular lymphonodus. Localized redness was found on the maxilla, namely the gingiva. Haematological examination revealed anaemia. Radiographic examination showed a mass on the left side of the face which made the boundaries unclear. Histopathologic examination showed hyperplasia. Based on anamnesis, clinical examination, and supporting examination, the case cat was suspected to have a tumor. The therapy given was anti-inflammatory drug meloxicam. Supportive therapy was given in the form of blood enhancement supplements in the form of Fufang E'jiao Jiang. However, chemotherapy to cure the tumor could not be given because the cat died. Samples of the cat's swollen face were taken and found to be peripheral ossifying fibroma. In addition, before death the cat had diarrhoea and vomited worms. Therefore, it is important to check the cat's health condition regularly, especially the mouth to ensure that the cat is healthy.